2012
DOI: 10.1016/j.jfa.2011.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Estimates for the square variation of partial sums of Fourier series and their rearrangements

Abstract: We investigate the square variation operator V 2 (which majorizes the partial sum maximal operator) on general orthonormal systems (ONS) of size N . We prove that the L 2 norm of the V 2 operator is bounded by O(ln(N )) on any ONS. This result is sharp and refines the classical Rademacher-Menshov theorem. We show that this can be improved to O( ln(N )) for the trigonometric system, which is also sharp. We show that for any choice of coefficients, this truncation of the trigonometric system can be rearranged so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(48 citation statements)
references
References 11 publications
0
48
0
Order By: Relevance
“…Inequality (1.21) replaces the fractional integration argument from [8] (as it is not clear if this argument is available in the discrete setting) and allows us to obtain (1.12) for p ∈ (3/2, 2]. A variant of this inequality was proven by Lewko-Lewko [12,Lemma 13] in the context of variational Rademacher-Menshov type results for orthonormal systems and it was also obtained independently by the second author and Trojan [15,Lemma 1] in the context of variational estimates for discrete Radon transforms, see also [14]. Inequality (1.21) reduces estimates for a supremum or an r-variation restricted to a dyadic block to the situation of certain square functions, where the division intervals over which differences are taken (in these square functions) are all of the same size.…”
Section: 4mentioning
confidence: 99%
“…Inequality (1.21) replaces the fractional integration argument from [8] (as it is not clear if this argument is available in the discrete setting) and allows us to obtain (1.12) for p ∈ (3/2, 2]. A variant of this inequality was proven by Lewko-Lewko [12,Lemma 13] in the context of variational Rademacher-Menshov type results for orthonormal systems and it was also obtained independently by the second author and Trojan [15,Lemma 1] in the context of variational estimates for discrete Radon transforms, see also [14]. Inequality (1.21) reduces estimates for a supremum or an r-variation restricted to a dyadic block to the situation of certain square functions, where the division intervals over which differences are taken (in these square functions) are all of the same size.…”
Section: 4mentioning
confidence: 99%
“…The variation norm on the left-hand side of (2.6) can be extended to all t ∈ [0, 2 k ] if g : [0, 2 k ] → C is continuous. Lemma 2.5 originates in the paper of Lewko and Lewko [LL12], where it was observed that the 2-variation norm of a sequence of length N can be controlled by the sum of log N square functions and this observation was used to obtain a variational version of the Rademacher-Menshov theorem. Inequality (2.6), essentially in this form, was independently proved by the first author and Trojan in [MT16] and used to estimate r-variations for discrete Radon transforms.…”
Section: Introductionmentioning
confidence: 99%
“…A variational variant of this inequality was proven by Lewko-Lewko [11,Lemma 13] in the context of variational Rademacher-Menshov theorems. It was also obtained independently by the first two authors in [15] in the context of variational estimates for discrete Radon transforms, see also [14].…”
Section: Basic Numerical Inequalitymentioning
confidence: 98%
“…(ii) A maximal estimate in terms of dyadic sub-blocks (see (2.7)). It is a consequence of a numerical maximal estimate (see Lemma 2.3), which in turn is an outgrowth of the idea implicit in the proof of the classical Rademacher-Menshov theorem (see [21] and also [11] and [15]). (iii) A refinement of the estimates for multi-dimensional Weyl's sums in [19], where the previous limitations N ǫ ≤ q ≤ N k−ǫ are replaced by the weaker restrictions (log N ) β ≤ q ≤ N k (log N ) −β for suitable β.…”
Section: Introductionmentioning
confidence: 94%